Optimasi Game AI Pada Game Strategi dengan Menggunakan Algoritme Genetik - Tio Allin Subiantoro; Wibisono Sukmo Wardhono; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Artificial Intelligence in video games is made to offer a challenge for the players. However, most of the AI only use simple rules to decide where to move. Those simple rules are the distance between the other opponent's unit, attack range, unit's power, etc. This kind of behavior is usually predictable and tend to be exploited easily. Genetic algorithm is an algorithm that provides various solutions to a certain problem. Thus, in this research, we use a genetic algorithm to control the unit movements. The algorithm will evaluate various factors before it is going to decide on where to move. These factors are the potential damage, potential loss, the distance of each unit to the midpoint, and the distance to the enemy main headquarter. Based on the research result, we can conclude that using a genetic algorithm as an artificial intelligent agent prove that the movement pattern of the units are less predictable. Additionally, they will still try to satisfy the goal given to them.